FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKS BERISIKO PEMANDU KARAOKE TETAP DI KOTA TEGAL - Beta Yuananda; Kusyogo Cahyo; Emmy Riyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
In tegal city there are 8 karaoke places with 180 karaoke guides, 2 of them positive HIV and 40% karaoke guide struck with IMS in 2015. The purpose of this research is to analyze the factors that corelate with karaoke guide's sex behavior in tegal. The method that used is quantitatif with cross sectional approach. Population of this research is 57 karaoke guide of 3 karaoke places with sampling tecnique, simple random sampling. Data analysis method using univariat and bivariat analysis. The result of univariat analysid is mature category respondents with the sex behaviour 43,9%, (25-30 years old) 54,4%, senior highschool graduated 50.9%, hugh payment 82.5%, marital status 61,4%, bad knowledge 57.6%, impolitenes/bad attitude 50.9%, inavaolability of infrastucture 52,6%, availability of information. And 56,1% get external support to do a risk sex behavior. Meanwhile, the reasercher do the bivariat analysis with chi-square statistics test. (significance 0.05). The result of chi-square test shows the variable that corelate with the risk behavior of karaoke guide is knowledge (p=0.029), attitude (p=0.044), availability of information (p-value=0.002), external support (p-value=0.024). Whereas the variable that irelated is ages (p=0,628), education (p=0.677), salary (p=0.070), marital status (p=0.641) and the availability of infrastructure (p=1.000)